Credit Dynamics and Macroeconomic Stability in Indonesia: Evidence from ARDL–ECM - Citra Rahayu Indraswari; Girindra Mega Paksi; Yudi Krisdianto (SAFE-Network, 2026)
This study examines the effects of money supply, exchange rate, inflation, and interest rate on bank credit in Indonesia using monthly time-series data from January 2004 to December 2024. The study applies the Autoregressive Distributed Lag approach and the Error Correction Model to distinguish short-run dynamics from long-run relationships. The selected ARDL model shows that money supply has a positive and significant short-run effect on bank credit, highlighting the role of liquidity in banking intermediation. Exchange rate movements exert significant lagged effects, suggesting that external monetary pressures influence credit gradually. Inflation negatively affects bank credit with a lag, indicating that price instability may weaken credit expansion. Conversely, the interest rate is not retained in the optimal model, implying a weaker direct transmission effect. The Bounds Test does not confirm cointegration, suggesting no stable long-run equilibrium. Overall, Indonesian bank credit is more responsive to short-run macroeconomic fluctuations than to persistent long-run relationships during the period.